Putala Naach and Wayang: Ramayana Tradition in Puppet Theatre in Assam and Bali - Saswati D Bordoloi (Universitas Indraprasta PGRI, 2021)
The Ramayana is not only a Hindu epic, it is a symbol of truth, victory over evil, and this is the reason the main route of the epic has accepted by many countries along with India also. Many local parts of Ramayana have also recognised. Not only in literature, but the Ramayana tradition has preserved in performing art form also. Bali of Indonesia is one of the tourist attraction places for its tradition, culture, and puppetry. Besides the local version of Ramayana, through the Wayang (puppet) the Ramayana has been preserved in Bali. For thousands of years, the stories of Rama, Sita, Hanoman and Ravana have been told in Java and Bali in Indonesia, and thru Wayang (Wayang Kulit and wayang Golek) the Ramayana tradition has been performing. In the North-eastern state of India in Assam, the Ramayana tradition has been performing thru Putala Naach (puppet). The Ramayana tradition has been preserved in two different puppetry forms. In Bali, the Ramayana tradition has performed in shadow puppet (Wayang Kulit), but in Assam, the Ramayana tradition has been performing thru string puppet. Though there is a vast difference between Wayang and Putala Naach, this paper has tried to examine the relationship between them thru the stories of Ramayana, the repertoires, the puppeteers, the beginning rituals, and the musical accompaniments.